Knowledge of cervical cancer prevention and treatment, and willingness to receive HPV vaccination among college students in China - Zhang, Fengzhi; Li, Manman; Li, Xiaoxue; Bai, Hua; Gao, Jinling; Liu, Hua (BMC public health, 2022)
Cervical cancer is the fourth most common cancer in women. Up to 99% of cervical cancer cases are associated with high-risk human papillomavirus (HPV). Sexual behavior is a direct risk factor for HPV infection, and sexually active college students, therefore, receive attention for HPV vaccination. At present, most Chinese studies lack of in-depth research on influencing factors, and are limited to cervical cancer, HPV, or HPV vaccine, without comprehensive consideration. This study investigated Chinese college students' cervical cancer prevention and treatment knowledge level, and explored the influencing factors, and understood their willingness to receive HPV vaccination. The findings of this study will lay a foundation for promoting the early screening of cervical cancer and vaccination process. A total of 800 college students from four universities in Zhengzhou, China were selected by multistage random sampling method. A self-administered questionnaire on the knowledge of cervical cancer prevention and treatment, and willingness to receive HPV vaccination was carried out. A logistic regression model was conducted to analyze factors influencing knowledge of cervical cancer prevention and treatment among college students. Up to 87.9% of college students said they had heard of cervical cancer. The proportion of college students with good knowledge of cervical cancer prevention and treatment was 46.7%. Logistic regression showed that gender, major, grade, level of education, the father's level of education, premarital sex attitude, and mother cervical cancer screening participation had a significant influence on cervical cancer prevention and treatment knowledge level (P < 0.05). In addition, 589 (74.0%) of college students had heard of HPV vaccine, and 92.8% of college students said they were willing to get vaccinated or recommended that their relatives and friends get vaccinated. The knowledge level of cervical cancer prevention and treatment knowledge among college students in Zhengzhou is low. Many of them had poor knowledge about HPV vaccine, but their willingness to vaccination is high. Various health education modes should be carried out for people with different characteristics, to improve their knowledge of cervical cancer prevention and promote the vaccination process.